2: Impact of Admission Temperature on Mortality and Major Morbidities in Very Preterm Infants. Issue 6 (1st June 2014) - Lyu, Y; Shah, PS; Ye, XY; Piedboeuf, B; Deshpandey, A; Dunn, M; Lee, SK
Abstract: BACKGROUND: There have been limited investigations of the influence of admission body temperature on neonatal outcomes. Optimal ranges of admission temperature associated with mortality and morbidity are still unclear. OBJECTIVES: To examine the impact of admission temperature on adverse neonatal outcomes and to identify optimal ranges of temperature in very preterm infants. DESIGN/METHODS: Inborn neonates with gestational age <33 weeks admitted to Neonatal Intensive Care Units (NICUs) in Canadian Neonatal Network between 2010 and 2012 were included. Neonates with major congenital anomalies were excluded. The admission temperature measured within 5 h after admission to NICU was classified into nine groups starting from <34.5°C to ≥38°C with 0.5°C increment. The composite outcome was defined as mortality or any major morbidity including bronchopulmonary dysplasia(BPD), necrotizing enterocolitis(NEC), nosocomial infection(NI), severe intraventricular haemorrhage or periventricular leukomalacia and severe retinopathy of prematurity (ROP). The relationship between admission temperature and composite outcome and individual components of composite outcome identified in univariate analyses were further examined and used to determine the optimal temperature range using multivariable analyses. RESULTS: Of all 9833 neonates, 12%, 24%, 38%, 19%, 5%, and 2% of neonates had admission temperature <36°C, 36°C to 36.4°C, 36.5°C to 36.9°C, 37°C to 37.4°C, 37.5°C to 37.9°C, ≥38°C respectively. After adjustment for related maternal and infants characteristics, admission temperature was inversely related to mortality (19.5% increase per 0.5°C decrease) and a significant 'U' shaped relationship between admission temperature and composite outcome, NEC, ROP, BPD, and NI was observed, respectively .The rates of composite outcome, NEC, ROP, BPD, NI were lowest when the admission temperature was between 36.5°C and 37.4°C. CONCLUSIONS: Admission temperature in very preterm infants is associated with mortality and major morbidities. The optimal admission temperature in preterm infants ranged between 36.5°C and 37.4°C. This is the first outcome-based and population-based study in our knowledge with findings of optimal range of temperatures in very preterm infants consistent with WHO's recommendations.